Novel gas measurement based on pressure triggered release cycles for biochemical methane potential tests - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2021)
This study aims to present a novel gas counter and to demonstrate its suitability for biochemical methane potential tests. In this system, the gas to be measured is collected in a chamber enclosed with two one-way solenoid valves and the absolute pressure is continuously monitored. After a trigger pressure is reached, a portion of the gas is released and the amount of the released gas is calculated according to ideal gas law and recorded. Three iterations of the supervisory control and data acquisition unit were constructed and tested for BMP measurement. Although it can be further improved and variations are possible, the presented final version works with eight reactors simultaneously and the recommended maximum gas flow is 1.24 mL/min. For those reactors, the measured/ theoretical BMP ratio was 65.3% with 4.2% standard uncertainty, which is subjectively acceptable. Therefore, it can be concluded that the concept is valid and applicable to BMP tests.
Keywords: anaerobic digestion; biogas; BMP; gas counter; BIOGAS PRODUCTION; CO-DIGESTION; METER; FLOW; SYSTEM; SALIX